2020
DOI: 10.1111/psyp.13624
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dispositional restrictiveness on physiological markers of challenge and threat during a hypothetical transitional period in romantic relationships

Abstract: Restrictiveness, a component of relationship dominance associated with monitoring and regulating partners' behavior, is a risk factor and accelerant of Intimate Partner Violence (IPV). Few studies, however, have examined in vivo physiological responses associated with restrictiveness. Toward this end, 105 romantic couples (N = 210) completed measures of restrictiveness and had their physiological responses recorded in anticipation of and during a dyadic interaction in which they discussed a hypothetical transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This sample has been used before to examine how (a) cardiovascular responses indicating threat impact partners’ responsiveness (Peters, Reis, & Jamieson, 2018), and (b) how individuals’ restrictiveness or dominance can exacerbate physiological responses indicating threat (Tudder, Gresham, Peters, Reis, & Jamieson, 2020). However, the linear or curvilinear effects of support providers’ expressive suppression and attachment anxiety on partners’ outcomes has never been reported.…”
Section: Methodsmentioning
confidence: 99%
“…This sample has been used before to examine how (a) cardiovascular responses indicating threat impact partners’ responsiveness (Peters, Reis, & Jamieson, 2018), and (b) how individuals’ restrictiveness or dominance can exacerbate physiological responses indicating threat (Tudder, Gresham, Peters, Reis, & Jamieson, 2020). However, the linear or curvilinear effects of support providers’ expressive suppression and attachment anxiety on partners’ outcomes has never been reported.…”
Section: Methodsmentioning
confidence: 99%
“…Our secondary research question focuses on how power is associated with self‐reported appraisals of resources and demands before and after the conversation. Despite past research demonstrating that appraisals of resources and demands do not necessarily occur through conscious processes (Blascovich & Mendes, 2010; Jamieson, 2017) and, therefore, might not be consistent with physiological markers of these appraisals (Peters & Jamieson, 2016; Tudder et al, 2020), research reliably links higher power with more approach‐oriented motivation and behavior (Keltner et al, 2003; Overall et al, 2022) and with reduced fear and anxiety during social stressors (Schmid & Schmid Mast, 2013). Therefore, we predicted that higher power would be associated with self‐reported appraisals of greater coping resources relative to situational demands (i.e., greater challenge and less threat).…”
Section: Introductionmentioning
confidence: 94%
“…For example, if high-power partners typically approach problem-oriented discussions with their partner (i.e., tend to adopt the "discloser" role; Gable & Impett, 2012;Keltner et al, 2003), they may react differently when placed in the responder role than in the discloser role. Indeed, previous research using a similar protocol has found conversation role to be a moderating factor between trait measures of dominance and physiological reactivity (Tudder et al, 2020). However, research by Tudder and colleagues (2020) focused on a discussion between partners involving a hypothetical relationship transition, not an extra-dyadic problem discussion.…”
Section: The Current Studymentioning
confidence: 99%
See 2 more Smart Citations